Preclinical pharmacokinetic evaluation of novel antimalarial and antituberculosis drug leads - Strydom, Natasha (Department of Chemistry, 2019)
Preclinical pharmacokinetics relies on efficient and accurate screening to select clinical candidates from early leads. Poor pharmacokinetic interpretation can disadvantage drug discovery by promoting inadequate compounds and expelling potential drug candidates. Objectives of this project included pharmacokinetic evaluation of antimalarial and anti-tuberculosis lead compounds with techniques aimed at improving preclinical pharmacokinetic outcomes. This included mechanistic pharmacokinetic approaches such as non-linear mixed effects (NLME) modelling in comparison with traditional non-compartmental analysis. Where appropriate, pharmacokinetic methods were expanded to include organ distribution and capsule dosing in mice to bridge our techniques from discovery to early development. Three benzoxazole amodiaquine analogues possessing equipotent in vitro antiplasmodial activity and showed diverse in vivo efficacy in a malaria mouse model. Evaluation of their respective pharmacokinetics in mice showed their in vivo exposures could translate to in vivo efficacy. Retrospective PK/PD simulations point to a time above IC50 drive in efficacy. Pharmacokinetic evaluation of an aminopyridine antimalarial compound in its cyclodextrin inclusion complex revealed a pH dependent increase in solubility that reduced variance, likely due to favoured intestinal absorption. Investigation of two novel fusidic acid C-3 ester prodrugs aimed at repositioning fusidic acid for tuberculosis, showed high concentrations of the rodent specific 3-epifusidic acid metabolite that greatly reduced exposure of fusidic acid in mice. Further organ distribution studies showed a prodrug strategy is still viable for repositioning fusidic acid for tuberculosis, but that rodent models are inappropriate for further evaluation. NLME modelling successfully provided unique mechanistic and mathematical insight of pharmacokinetic profiles of new leads. The level of interpretation on pharmacology parameters improved and aided in understanding why drug leads are likely to fail or succeed, assisting future compound optimisation.